2022
DOI: 10.1177/23333928221104644
|View full text |Cite
|
Sign up to set email alerts
|

Association of Early and Late Hospital Readmissions with a Novel Housing-Based Socioeconomic Measure

Abstract: Background While socioeconomic status has been linked to hospital readmissions for several conditions, reliable measures of individual socioeconomic status are often not available. HOUSES, a new measure of individual socioeconomic status based upon objective public data about one's housing unit, is inversely associated with overall hospitalization rate but it has not been studied with respect to readmissions. Purpose To determine if patients in the lowest HOUSES quartile are more likely to be readmitted within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
(100 reference statements)
0
0
0
Order By: Relevance
“…This finding aligns with data from the Medicaid Nationwide Readmissions Database (NRD) in the U.S. in 2016-2020, indicating that individuals aged 45-64 had the highest percentages of readmissions (21.4 and 19.7 per 100 index admissions) [34]. A study involving approximately 12,000 people across various departments, including surgery, trauma, and internal medicine, reported an average age of 63.6 among those readmitted within 30 days [35], which closely mirrors our study However, a study by Jing Cao et al in China in 2021 revealed that majority of people readmitted due to pulmonary tuberculosis were over 65 years old. Additionally, according to Leppin et al's meta-analysis, the readmission rate tends to be higher in individuals older than 65 [24,25].…”
Section: Discussionmentioning
confidence: 62%
“…This finding aligns with data from the Medicaid Nationwide Readmissions Database (NRD) in the U.S. in 2016-2020, indicating that individuals aged 45-64 had the highest percentages of readmissions (21.4 and 19.7 per 100 index admissions) [34]. A study involving approximately 12,000 people across various departments, including surgery, trauma, and internal medicine, reported an average age of 63.6 among those readmitted within 30 days [35], which closely mirrors our study However, a study by Jing Cao et al in China in 2021 revealed that majority of people readmitted due to pulmonary tuberculosis were over 65 years old. Additionally, according to Leppin et al's meta-analysis, the readmission rate tends to be higher in individuals older than 65 [24,25].…”
Section: Discussionmentioning
confidence: 62%